A Bioorthogonal Small‐Molecule‐Switch System for Controlling Protein Function in Live Cells1. Issue 38 (25th July 2014) - Liu, Peng; Calderon, Abram; Konstantinidis, Georgios; Hou, Jian; Voss, Stephanie; Chen, Xi; Li, Fu; Banerjee, Soumya; Hoffmann, Jan‐Erik; Theiss, Christiane; Dehmelt, Leif; Wu, Yao‐Wen
Abstract Chemically induced dimerization (CID) has proven to be a powerful tool for modulating protein interactions. However, the traditional dimerizer rapamycin has limitations in certain in vivo applications because of its slow reversibility and its affinity for endogenous proteins. Described herein is a bioorthogonal system for rapidly reversible CID. A novel dimerizer with synthetic ligand of FKBP′ (SLF′) linked to trimethoprim (TMP). The SLF′ moiety binds to the F36V mutant of FK506‐binding protein (FKBP) and the TMP moiety binds to E. coli dihydrofolate reductase (eDHFR). SLF′‐TMP‐induced heterodimerization of FKBP(F36V) and eDHFR with a dissociation constant of 0.12 μM. Addition of TMP alone was sufficient to rapidly disrupt this heterodimerization. Two examples are presented to demonstrate that this system is an invaluable tool, which can be widely used to rapidly and reversibly control protein function in vivo.